Mediadores inflamatorios y su influencia en la evolución del cáncer colorrectal - de la Fuente L, Marjorie; Hermoso R., Marcela; Abedrapo M., Mario; Carrillo G., Katya; López N., Sebastián (Revista Hospital Clínico Universidad de Chile, 2017)
Colorectal cancer (CRC) is one of the most important causes of death from cancer worldwide, and in Chile, the mortality rate has increased considerably in recent years. Locally, diverse cells of the immune system can infiltrate the tumor, generating a tumor microenvironment and playing an important role in cancer progression. Inflammatory cells that infiltrate the tumorsecrete cytokines and chemokines, inflammatory mediators, which activate immune networks and participate in the control of proliferation and survival of malignant cells, and processes such as angiogenesis and metastasis. Thus, elevated levels of various inflammatory mediators, such as TNF-α, IL33 / ST2 cytokines, chemokines such as CCL3 and CCL4 have been detectedin different types of neoplasms, including CCR. The inflammatory reaction and changes in the levels of inflammatory mediators at the tumor site could account for the evolution of cancer, making them attractive the future predictive markers of disease or possible therapeutic targets. Therefore, in this review we emphasize in cytokines and chemokines involved in CRC and its association with carcinogenic mechanisms and tumor progression